Chronic Pain One to Five Years after Lung Transplantation - A. Forsberg; M Claëson; G-B Dahlman; A Lennerling (Journal of Organ Transplantation, 2017)
Chronic bodily pain after lung transplantation has received little attention. Therefore, the aim was to provide a multidimensional assessment of self-reported chronic pain 1-5 years after lung transplantation and its relationship with self-reported psychological general well-being (PGWB) and self-efficacy. This multicenter, cross-sectional study is a part of the Swedish national study: Self-management after thoracic transplantation (SMATT). In total, 117 lung transplant recipients, all white, due for their yearly follow-up at one (n=35), two (n=28), three (n=23), four (n=20) or five years (n=11) after transplantation were included. Of these, 113 reported their pain on the Pain-O-Meter (POM), which provides information about pain intensity, quality, location, and duration. In addition, they responded to the PGWB instrument and the Self-Efficacy instrument for managing chronic disease. The prevalence of pain was 51% after 1 year, 68 % after 2 years, 69.5 % after 3 years, 75 % after 4 years and 54.5 % after 5 years. Women experienced higher pain intensity and worse sensory and affective burden than men. Psychological general well-being was the main factor that contributed to the experience of pain. Better perceived psychological well-being lowered the odds for pain, while higher self-efficacy reduced the probability of experiencing pain. Many of the lung recipients lacked pain treatment and were uncertain about the reasons behind their pain. Chronic bodily pain is a common and serious symptom up to five years after lung transplantation. Female lung recipients experience more pain and pain related illness than men.
Keywords: Lung transplantation